Determinan Pembelian Melalui Digipay: Perspektif Pelaku Pengadaan Barang/Jasa pada Satuan Kerja - Wibawa, Dwi Ari; Amrullah, Muchamad; Hakim, Lukman; Sukmono, Renny (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2024)
Since its introduction in the fourth quarter of 2019, the utilization of Digipay until June 2022 has only reached IDR42.5 billion. This transaction value is relatively small when compared to the expenditure through e-purchasing, which amounted to IDR45,441 trillion. This situation has drawn the author's attention to analyze the factors influencing purchases through Digipay. The data used in this analysis is primary data. The analysis method employs descriptive statistics and Structural Equation Modeling. The sample size consists of 328 procurement actors in the regional work units (satker) of the Directorate General of Customs and Excise in South Kalimantan, Bali, DKI Jakarta, South Sulawesi, and Maluku. Overall, the quality of Digipay has received a satisfactory assessment, but there are some variables perceived at a relatively low level. One of the variables that received a low perception rating is the provider's ability to maintain the confidentiality of information during transactions. The hypothesis testing results indicate that Information Quality, Perceived Privacy Protection, and Perceived Security Protection have a significant and positive impact on Consumer Trust. Perceived Privacy Protection and Consumer Trust have a significant and positive impact on Perceived Risk. Information Quality and Perceived Security Protection have a significant and negative impact on Perceived Risk. Consumer Trust, Perceived Benefit, and Managerial Intervention have a positive and significant impact on Intention to Purchase. Information Quality, Perceived Privacy Protection, and Perceived Security Protection have a negative and significant impact on Intention to Purchase. Intention to purchase has a positive and significant impact on actual purchases. Based on this data and analysis, to enhance the acceptance of Digipay among procurement actors, the policy implications include improving information quality, emphasizing the assurance of user and transaction information security, minimizing usability difficulties of Digipay, requiring intervention from the Directorate General of Treasury, and integrating Digipay with the government procurement information system (LKPP) to facilitate tax collection.